2021
DOI: 10.3389/fdata.2021.652153
|View full text |Cite
|
Sign up to set email alerts
|

Housing Prices and the Skills Composition of Neighborhoods

Abstract: In the United States (US), low-income workers are being pushed away from city centers where the cost of living is high. The effects of such changes on labor mobility and housing price have been explored in the literature. However, few studies have focused on the occupations and specific skills that identify the most susceptible workers. For example, it has become increasingly challenging to fill the service sector jobs in the San Francisco (SF) Bay Area because appropriately skilled workers cannot afford the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Existing literature has emphasized the significance of establishing a balance between public interest, governmental constraints, and private sector interests. Meanwhile, several studies on bay areas emphasize the interaction between social policies such as the strong relationship between healthcare services, commercial establishments, labor employment, and travel attraction (Althobaiti et al, 2021). However, .…”
Section: Policy Implementation and Recommendationsmentioning
confidence: 99%
“…Existing literature has emphasized the significance of establishing a balance between public interest, governmental constraints, and private sector interests. Meanwhile, several studies on bay areas emphasize the interaction between social policies such as the strong relationship between healthcare services, commercial establishments, labor employment, and travel attraction (Althobaiti et al, 2021). However, .…”
Section: Policy Implementation and Recommendationsmentioning
confidence: 99%
“…The cost of living in a destination country often appears as a factor of migration, especially for highly skilled individuals, as potential migrants may be unwilling to migrate to a host country with the high level of prices (European Commission, 2018a; Malc et al, 2021;Gavurova et al, 2020b). However, other research results have indicated that highly skilled migrants tend to locate closer to the city centre, demonstrating their adaptation to the increase in average housing prices as opposed to low-skilled migrants that tend to locate further away (Althobaiti et al, 2021). Oliinyk et al (2021) argue that the migration of high-skilled people significantly contributes to the competitiveness of the countries and boosts economic development.…”
Section: Theoretical Backgroundmentioning
confidence: 99%